An Overview of Agricultural Pollution in Vietnam : Summary Report 2017 - Cassou, Emilie; Tran, Dai Nghia; Nguyen, Tin Hong; Dinh, Tung Xuan; Nguyen, Cong Van; Cao, Binh Thang; Jaffee, Steven; Ru, Jiang (World Bank, Washington, DC, 2018)
Vietnamese agriculture has experienced remarkable growth over the past twenty years. Today, however, Vietnamese agriculture is edging toward the limits of a growth model rooted more in the intensification of production systems featuring heavy use of labor, chemicals, and natural resources than in efficiency or value addition gains. Agricultural growth is decelerating and Vietnam’s competitiveness as a provider of bulk, undifferentiated commodities is flagging as the agricultural sector faces rising competition for labor, land, and other resources. The environmental fallout from intensification has also begun to adversely impact productivity and the position of Vietnam’s commodities in international markets. If it is to fulfill its ambitions and remain a motor of economic development, Vietnam’s agriculture will need to start producing More from Less. In this regard, tackling agricultural pollution represents a key challenge for Vietnam. Pollution has started to take a toll on the sector’s own resource base, potentially impacting soil fertility and yields, the effectiveness of chemicals in combating pests and disease, farmer health and productivity, environmental health, and the safety of food. Growing evidence and public concern about pollution have led the Vietnamese government to adopt a new outlook and to take measures to address the problem. The research upon which this summary report is based represents the first attempt to assemble existing evidence on the nature and magnitude of agricultural pollution in Vietnam, looking across the livestock, aquaculture, and crops subsectors. It is also an attempt to shed light on the socioeconomic impacts and drivers of agricultural pollution, including the shortcomings of existing policies and programs to reign in the problem.